Brace and Physiotherapeutic Scoliosis Specific Exercises (PSSE) for Adolescent Idiopathic Scoliosis (AIS) treatment: a prospective study following Scoliosis Research Society (SRS) criteria - Nikos Karavidas; Dionysios Tzatzaliaris (Archives of Physiotherapy, 2022)
Abstract Background A growing scientific evidence for conservative treatment of AIS has recently proved that bracing is superior to natural history. Our aim was to investigate the effectiveness of a combined treatment with brace and PSSE for AIS. Methods Prospective study, following SRS research inclusion criteria (> 10 years, 25ο – 40ο, Risser 0–2, < 1-year post-menarche, no prior treatment). 102 consecutive patients (87 females-15 males, mean age 12.8 years, Risser 0.48, Cobb Thoracic 29.2ο, Lumbar 27.8ο) received treatment with Cheneau brace and PSSE. Average follow-up time was 26.4 months. A scale from A to C was used to evaluate compliance with brace and PSSE (A: full-compliant, B: partially compliant, C: non-compliant). 7 subjects dropped-out (6.8%), so finally 95 patients included for statistical analysis, using paired t-test. Results Sixty-two patients (65.3%) remained stable, 22 improved > 5ο (23.2%) and 11 progressed (11.5%). In-brace correction (IBC) was 49.7% for thoracic and 61.7% for lumbar curves. Analysis of progressed cases revealed that IBC (31.7% for thoracic and 34.4% for lumbar curves) and compliance (81.8% C for brace, 63.6% C for PSSE) was lower than average. Group A for treatment compliance (65.3%), showed significantly better results (70.9% stable, 29.1% improved, 0% progressed). Conclusion A combination of bracing and PSSE can effectively treat AIS, according to SRS inclusion criteria. 88.5% of patients avoided progression > 5ο and only 6.4% overpassed 40ο. IBC and compliance are the most important prognostic factors for successful treatment result. Early detection of AIS is also necessary for increased possibilities of effective conservative treatment.